American Indians’ Attitudes Toward the Appropriateness of Use of Force by the Police - Redner-Vera, Erica (Crime & delinquency, 2024)
Individuals’ perceptions of law enforcement officers and their actions are important for understanding personal criminality, police legitimacy, and legal cynicism. Race and ethnicity play a role in shaping these perceptions, however little work has been done to understand American Indian perceptions. We employ the General Social Survey to assess how American Indians compare to individuals of other races regarding their approval of police use of force. American Indians are less supportive of police use of force than whites. However, when compared to other people of color, American Indians are more supportive of use of force across five different police-citizen types of encounters. We conclude by examining the importance of considering different racial and ethnic views on legal authority.